Comparative Analysis of Expected Return and Portfolio Risk in Formation of Optimal Portfolios Using the Capital Asset Pricing Model (Capm) and Single Index Methods: Analisis Perbandingan Expected Return dan Risiko Portofolio dalam Pembentukan Portofolio Optimal Menggunakan Metode Capital Asset Pricing Model (Capm) dan Indeks Tunggal - Elsa Veronica Putri; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine how the ratio of expected return and portfolio risk in the formation of an optimal portfolio using the Capital Asset Pricing Model (CAPM) and Single Index methods. This study uses a quantitative approach. The object of this research is the LQ45 stock for the 2017-2019 period. The research sample amounted to 30 companies selected through purposive sampling technique. The results showed that the optimal portfolio formed using the Capital Asset Pricing Model (CAPM) and Single Index methods resulted in 7 candidate stocks consisting of ICBP, BBCA, JSMR, SMGR, BBRI, MNCN, INCO. Where the results of the calculation of the level of the expected return of the portfolio using the Capital Asset Pricing Model (CAPM) method is 0.0241 and the portfolio risk level is 0.010. Meanwhile, the level of portfolio expected return using the single index method is 0.0372 and the portfolio risk level is 0.0136. After the independent t-test was carried out, there was no difference in the expected return of the portfolio between the Capital Asset Pricing Model (CAPM) and Single Index methods, while in portfolio risk testing there were differences between the CAPM and Single Index methods.